1997
DOI: 10.2307/3433514
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils Amplify the Formation of DNA Adducts by Benzo[a]pyrene in Lung Target Cells

Abstract: Inflammatory cells and their reactive oxygen metabolites can cause mutagenic effects in lung cells. The purpose of this study was to investigate the ability of activated neutrophils to modulate DNA binding of benzo[a]pyrene (B[a]P), a known carcinogen, in lung target cells. Equivalent numbers of rat lung epithelial cells (RLE-6TN cell line) and freshly isolated human blood neutrophils (PMN) were coincubated in vitro for 2 hr after addition of benzo[a]pyrene (0.5 microM) or two of its trans-diol metabolites, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 6 publications
(6 reference statements)
1
7
0
Order By: Relevance
“…Again, this effect was shown to be MPO dependent (143). More recently, these observations were confirmed by studies in our laboratory, showing that activated neutrophils enhance BPDE-DNA adduct formation in co-cultured alveolar epithelial target cells that were exposed to B[a]P-7,8-dihydrodiol (144).…”
Section: Activation Of Pahs By Neutrophil-derived Mposupporting
confidence: 64%
See 1 more Smart Citation
“…Again, this effect was shown to be MPO dependent (143). More recently, these observations were confirmed by studies in our laboratory, showing that activated neutrophils enhance BPDE-DNA adduct formation in co-cultured alveolar epithelial target cells that were exposed to B[a]P-7,8-dihydrodiol (144).…”
Section: Activation Of Pahs By Neutrophil-derived Mposupporting
confidence: 64%
“…Cigarette smoke is a potent source of chemical carcinogens and, at present, it is believed that the association between MPO and pulmonary carcinogenesis can be explained by the involvement of neutrophil-derived MPO in metabolic activation of inhaled chemical carcinogens, including aromatic amines (157)(158)(159) and heterocyclic amines (133). However, MPO activity has most frequently been linked to the metabolism of carcinogenic polycyclic aromatic hydrocarbons (PAHs) (126,(141)(142)(143)(144).…”
Section: Metabolic Activation Of Chemical Carcinogens By Neutrophilsmentioning
confidence: 99%
“…A requirement for exogenous DNA damage was surprising considering previous studies that suggested that the inflammatory response increases the effectiveness of PAHs, such as BaP, to form DNA adducts, not to mention DNA damage induced directly through the inflammatory response (Shacter et al, 1988; Borm et al, 1997; Zhuang et al, 2002; Kim & Wogan, 2006). Although this would suggest that inflammation alone or in the presence of BaP could lead to increased mutagenic lesions, we failed to observe such an effect.…”
Section: Discussionmentioning
confidence: 99%
“…They established an in vitro system for co-incubation of neutrophils and hamster V79 cells, and showed that reactive intermediates generated by neutrophil-mediated metabolism of BP-7,8-dihydrodiol (a proximate activated metabolite of BP) can induce sister chromatid exchanges in the V79 cells. Borm et al (1997) carried out similar experiments using co-incubations of human blood neutrophils and a rat epithelial lung cell line. Petruska et al (1992) showed that MPO can activate BP-7,8-dihydrodiol in the mouse lung in vivo, as measured by formation of DNA adducts.…”
mentioning
confidence: 99%